More than a footwedge: Golf-specific footwear alters muscle activation patterns during standing balance - Wilson, S. J.; Gdovin, J. R.; Williams, C. C.; Donahue, P. T.; Mouser, J. G.; Mutchler, J. A.; Simpson, J. D.; Chander, H.; Garner, J. C. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2022)
Within a golf swing, one aspect that stands out in each phase is the ability to maintain balance. Previous reports suggest that extrinsic factors, such as footwear, and intrinsic factors, such as muscular exertion level, have detrimental effects on human postural control. However, no studies have examined the effects of modern golf footwear on muscle activity of the lower extremity. Thus, the purpose of this study was to examine differences in muscle activity when walking for extended durations in golf footwear. Participants were tested for balance prior to walking sessions and then every 60 min until the 240th minute in three types of golf footwear; dress shoes, tennis shoes, and casual shoes, and barefoot. Mean muscle activity during balance testing of the vastus medialis, semitendinosus, tibialis anterior, and medial gastrocnemius was examined using a 4 × 5 repeated measures analysis of variance to identify differences within time and footwear types. Increases in muscle activity were observed after the second hour. Footwear differences were observed in the dress shoe and tennis shoe style relative to the casual style, and primarily attributed to the increased sole/midsole thickness, and increased mass of the dress shoe. These results suggest that golf footwear characteristics may alter muscle activity patterns during standing balance.